Population dynamics of freshwater Gastropod Chilina fluminea (Chilinidae) in a temperate climate environment in Argentina - Gutierrez Gregoric, Diego Eduardo (2012)
The presence and density of gastropods, and the individual growth rate of Chilina fluminea snails at Rıo de la Plata beach, Berisso, Buenos Aires province, Argentina, were analyzed to obtain population data about hosts that could be useful for control of the free-swimming larval stages (cercariae). Chilina fluminea has a unique annual reproductive period during winter, whereas other gastropods inhabiting the same area reproduce one to three times a year, but never in winter. Thus, autumn, the season before reproduction and oviposition, is the most adequate season for taking actions to regulate the size of C. fluminea populations to reduce possible cases of human schistosomic dermatitis.